Social Fear Conditioning Paradigm in Virtual Reality: Social vs. Electrical Aversive Conditioning - Reichenberger, Jonas; Porsch, Sonja; Wittmann, Jasmin; Zimmermann, Verena; Shiban, Youssef (Frontiers in Psychology, 2017)
In a previous study we could show that social fear can be induced and extinguished using virtual reality (VR). In the present study, we aimed to investigate the belongingness effect in an operant social fear conditioning (SFC) paradigm which consisted of an acquisition and an extinction phase. Forty-three participants used a joystick to approach different virtual male agents that served as conditioned stimuli. Participants were randomly allocated to one of two experimental conditions. In the electroshock condition, the unconditioned stimulus (US) used during acquisition was an electric stimulation. In the social threat condition, the US consisted of an offence: a spit in the face, mimicked by a sound and a weak air blast to the participant’s neck combined with an insult. In both groups the US was presented when participants were close to the agent (75% contingency for CS+). Outcome variables included subjective, psychophysiological and behavioral data. As expected, fear and contingency ratings increased significantly during acquisition and the differentiation between CS+ and CS- vanished during extinction. Furthermore, a clear difference in skin conductance between CS+ and CS- at the beginning of the acquisition indicated that SFC had been successful. However, a fast habituation to the US was found towards the end of the acquisition phase for the physiological response. Furthermore, participants showed avoidance behavior towards CS+ in both conditions. The results show that social fear can successfully be induced and extinguished in VR in a human sample. Thus, our paradigm can help to gain insight into learning and unlearning of social fear. Regarding the belongingness effect, the social threat condition benefits from a better differentiation between the aversive and the non-aversive stimuli. As next step we suggest comparing social-phobic patients to healthy controls in order to investigate possible differences in discrimination learning and to foster the development of more efficient treatments for social phobia.